Hospital and long-term care facility environmental service workers' training, skills, activities and effectiveness in cleaning and disinfection: a systematic review. (June 2022) - Thomas, R.E.; Thomas, B.C.; Lorenzetti, D.; Conly, J.
Summary: Background: Multi-drug-resistant organisms (MDROs) (meticillin-resistant Staphylococcus aureus, vancomycin-resistant enterococcus, MDR Acinetobacter spp., extended-spectrum beta-lactamase-producing Gram-negative organisms), Clostridioides difficile, viral respiratory pathogens and healthcare-associated infections (HAIs) are major concerns in medical facilities. Aims: To assess environmental service workers' (ESWs) training, workload, numbers of surfaces and pieces of medical equipment cleaned per shift, how long they worked on each surface, how they cleaned, supervision, MDRO and HAI status, and measurement of effectiveness in reducing MDROs and HAIs in patients and on surfaces. Methods: CINAHL, Cochrane CENTRAL Register of Controlled Trials, EMBASE, Medline and Scopus were searched from inception to 28 th June 2021 (no language/date limits). Searches combined terms from three themes: (a) hospitals and acute/long-term care facilities (e.g. assisted living, long-term care facilities, nursing homes); (b) disinfectants (e.g. antisepsis, bleach, cleaning, copper plating of surfaces and copper impregnation of textiles, disinfection, decontamination, hydrogen peroxide, quaternary ammonium disinfectants, and ultraviolet rays); and (c) randomized controlled trials (RCTs). Findings and conclusions: Fourteen cluster RCTs provided data on a series of interventions. Ten trials focused on reducing patient infections from MDROs/HAIs, and four found significant reductions in patient infection rates with strategies including bleach, quaternary ammonium detergents, ultraviolet light and hydrogen peroxide vapour. Minimal information was provided on ESW numbers, MDRO/HAI status, workload, numbers of surfaces and objects cleaned per shift, and effects of training on improving effectiveness. The findings suggest that there is a need for detailed evaluations of the effects of training and disinfection activities for individuals and teams of ESWs.